Election campaigning on Facebook among Malaysian politicians in the 14th Malaysian General Election - Abdul Manan, Kamaruzzaman; Mohamed, Shafizan; Wan Mohd Ghazali, Wan Norshira (2019)
Politicians today are very much reliant on Facebook to communicate with the public and promote their political ideologies. Facebook was the most popular social media that been used in political communication during the last GE campaign period. In addition, due to its personalization, Facebook is seen as crucial medium for politician candidate to communicate directly with their voters. This allow the politician candidate to build a closer relationship and agenda in win the voters trust. In an attempt to explore how the politicians use Facebook during election campaigns, this study explored official Facebook posts by eight politicians during the 14th Malaysian General Election. The objectives of this study are to explore the political candidate pattern of using Facebook during election, to explore the issues highlighted by politicians in their personal Facebook account and to identify the type of posting political candidate use in their Facebook accounts. Content analysis of the politicians’ Facebook posts showed that the politicians strategically use Facebook to create and maintain a positive image rather than promoting issues and engaging in discussions with the public. The eight candidates differed in terms of the amount of posts they shared but had minor difference in the characteristics of their Facebook contents. In addition, politician candidate actively post information’s related to their campaign activities and use live streaming to broadcast their campaign speech. The candidates are more focused more on promoting their personal credibility as leaders suggesting that Facebook is encouraging the personalization of politics. This indicate that politician candidate used Facebook as the medium to influence the voters on what to think about.